Efektivitas Larva Black Soldier Fly (Maggot) dalam Mengatasi Permasalahan Sampah Organik - Syahid Ma'ruf Amir; Zahra Umi Fajrina; Rina Rahayu (Lembaga Bale Literasi, 2025)
The waste problem in Indonesia has become a serious problem. As much as 64.88% of the tens of millions of tons of waste per year is organic waste. Although classified as organic waste, this remains a major concern due to the various negative impacts caused by it. The purpose of this study was to explore the latest information regarding the effectiveness of maggots in overcoming the problem of organic waste. The research method used in writing this article is descriptive analysis with a literature study method. The results of the study indicate that maggots are able to decompose organic waste by actively eating it for 2-3 weeks for the growth process. By eating organic waste, these black soldier fly larvae are able to grow and develop well. Therefore, organic waste can be decomposed and reduced by making it into maggot feed. In addition, the maggots produced can also be used as feed for chickens, fish, or other animals. The remaining organic waste decomposition by maggots can also be used as organic fertilizer that fertilizes the soil. Thus, it can be concluded that black soldier fly larvae (maggots) have proven effective in overcoming the problem of organic waste.